2012
DOI: 10.1158/0008-5472.can-11-1070
|View full text |Cite|
|
Sign up to set email alerts
|

Deletion of the Endothelial Bmx Tyrosine Kinase Decreases Tumor Angiogenesis and Growth

Abstract: Bmx (Bone marrow kinase in chromosome X), also known as Etk, is a member of the Tec family of nonreceptor tyrosine kinases. Bmx is expressed mainly in arterial endothelia and in myeloid hematopoietic cells. Bmx regulates ischemia-mediated arteriogenesis and lymphangiogenesis, but its role in tumor angiogenesis is not known. In this study, we characterized the function of Bmx in tumor growth using both Bmx knockout and transgenic mice. Isogenic colon, lung, and melanoma tumor xenotransplants showed reductions i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…Also, we found significant decreases in the percent of ECs expressing pβ3-(Y759), in the intensity of phospho-BMX (BMX activation) and phospho-p130CAS in ECs, and in vessel surface area in the tumors of RGD-peptide treated mice as compared to controls (Figure 7F, 7H-7K). Phospho-BMX staining of ECs in the xenograft tumors was detected in a population of vessels, consistent with BMX expression in vessels of arterial origin [39, 40]. These data suggest that ECs interact with tumor cells in the perivascular niche through an RGD-peptide-binding integrin and that this interaction promotes BMX and p130CAS activation, thereby enhancing angiogenesis.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Also, we found significant decreases in the percent of ECs expressing pβ3-(Y759), in the intensity of phospho-BMX (BMX activation) and phospho-p130CAS in ECs, and in vessel surface area in the tumors of RGD-peptide treated mice as compared to controls (Figure 7F, 7H-7K). Phospho-BMX staining of ECs in the xenograft tumors was detected in a population of vessels, consistent with BMX expression in vessels of arterial origin [39, 40]. These data suggest that ECs interact with tumor cells in the perivascular niche through an RGD-peptide-binding integrin and that this interaction promotes BMX and p130CAS activation, thereby enhancing angiogenesis.…”
Section: Resultssupporting
confidence: 62%
“…In ECs co-seeded with CSCs, we found that integrin αvβ3 is necessary for BMX activation and that BMX is necessary for p130CAS activation whereas in ECs seeded in CM/EC+CSC, αvβ3 is not necessary for BMX activation and BMX is not necessary for p130CAS activation. BMX, a cytoplasmic non-receptor tyrosine kinase, can activate signaling pathways that promote migration and angiogenesis as well as other signaling pathways [39, 40, 4246]; thus, the increased BMX activity downstream of activated integrin αvβ3 in the ECs co-seeded with CSCs could serve to amplify and diversify signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Heterodimerization of HER4 with HER2 and subsequent downstream signalling, including the PI3K‐AKT pathway, plays a crucial role in heart physiology 103. As described in the previous section, also the ibrutinib‐binding protein BMX was shown to be of importance for the cardiovascular system 53. Thus, there are several possibilities for that ibrutinib's interaction with target proteins other than BTK could cause cardiac dysfunction and atrial fibrillation, and we favour the idea of an off‐BTK target mechanism.…”
Section: Consequences Of Ibrutinib Treatment Not Related To B Cellsmentioning
confidence: 95%
“…The samples were then mounted in mounting medium containing DAPI (Vector Laboratories). Frozen sections of the ventral skin (10 mm) were cut and stained as previously described (Holopainen et al 2012a).…”
Section: Immunofluorescent Staining and Microscopymentioning
confidence: 99%